Integration of Ecopedagogy in Elementary School Management as an Effort to Inculcate Environmental Insight Character Values for Generation Alpha - Wahyuddin, Erwansyah; Sullam, Muhammad Ridho; Amin, Muhammad Rasyid (Proceeding International Conference on Religion, Science and Education, 2022)
This study aims to determine the form of ecopedagogy integration in elementary school management as an effort to inculcate the character values of environmental insight for the alpha generation. This research is motivated by the problem of the alpha generation who are familiar with digital technology, but have little understanding of character values related to environmental insights, such as being efficient in using energy, reducing the use of plastic or single-use objects, to the importance of caring for and growing plants. for the survival of human life. Because they do not know and do not feel the beauty of nature and the surrounding environment because there are many significant environmental and life changes. A qualitative approach is applied in this study by reviewing literature and previous studies that can be used as a reference source in making ecopedagogical integration policies at the elementary school level (SD) with the hope of forming a generation that is insightful and has a love for the surrounding environment. The expected result in this research is to be able to show various kinds of reference sources for the application of ecopedagogy in creating integration in elementary schools as an effort to inculcate the character values of environmental insight for the alpha generation.